Implementasi Education Management Information System ( EMIS ) Dalam Mengelolah Data Lembaga Di Madrasah Tsanawiyah Darussa’adah Gubugklakah Kecamatan Poncokusumo Kabupaten Malang - Husnil Mubarok (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2021)
The rapid development and advancement of technology has made significant changes to the condition of society, both in terms of policy, communication, biocracy, or at any existing institutions, without exception educational institutions. Educational institutions are institutions that are directly affected by developments in the times and technology, so that educational institutions are required to be able to keep up with any changes and developments in the vicinity, especially technological developments. The Education Management Information System or known as EMIS is a form of technological development, which is useful in providing real data for educational institutions as a support in managing new useful data and information for its users using computers and internet networks. EMIS is a combination of human resources and other computer-based resources that produces cumulative data storage, recovery, communication, and use for the purpose of effective and efficient school management operations